Integrated cardiorespiratory system model with short timescale control mechanisms. (7th April 2020) - Fernandes, Luciano G.; Trenhago, Paulo R.; Feijóo, Raúl A.; Blanco, Pablo J.
Abstract: A compartmental model of the cardiorespiratory system featuring pulsatile blood flow and gas transport, as well as closed loop mechanisms of cardiorespiratory regulation is presented. Short timescale regulatory action includes baroreflex, peripheral and central chemoreflex feedback. The cardiorespiratory model is composed by compartments to describe blood flow and gas exchange in the major systemic and pulmonic regions. The control systems include formulations to afferent activity of arterial baroreceptor and peripheral and central chemoreceptors. Simulations described here include situations of hypoxia, hypercapnia, and hemorrhage. The overall responses of our simulations agree with physiological (experimental) and theoretical data. Our results suggest that the present model could be used to further understand the interplay among major regulatory mechanisms in the functioning of the cardiovascular and respiratory systems in cases of normal and abnormal physiological conditions. Abstract : A compartmental model of the cardiorespiratory system featuring pulsatile blood flow, gas transport, and closed loop mechanisms of cardiorespiratory regulation is presented. Short timescale regulatory action includes baroreflex, peripheral, and central chemoreflex feedback. Simulations described here include situations of hypoxia, hypercapnia, and hemorrhage. The present model could be used to further understand the interplay of major regulatory mechanisms in the functioning of the cardiovascular and respiratory systems in cases of normal and abnormal physiological conditions.